The Role of Midwife Therapeutic Communication With Anxiety Levels in Maternity at The Limboro Health Center in 2020 - Rusnawati Rusnawati; Muhammad Syafar; Sitti Maisuri Tadjuddin Chalid; Werna Nontji; Rosita Rosita (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Anxiety has an impact on the duration of the first and second stages of labor. Generally, anxiety during labor is caused by fear of giving birth. To reduce the level of anxiety, it is necessary to communicate with therapeutic midwives in creating good relationships with maternity mothers so that there is an exchange of information, feelings, and thoughts. This research aims to find the relationship between the therapeutic communication of midwives with the level of anxiety in maternity mothers. The research method uses a cross-sectional study with a sample of 30 maternity mothers who were selected based on the purposive sampling technique. The results of the study from 30 respondents, the percentage of mothers who received therapeutic communication was not good with mild anxiety levels as many as 4 respondents (66.7%), while at moderate and severe levels of anxiety each 1 respondent (16.7%). Bivariate analysis with chi-square test showed p-value = 0.014 with a significance level ofa = 0.05, where p < a (0.05)so it can be concluded that there is a relationship between the midwife's therapeutic communication with the level of maternal anxiety. It is recommended to manage the psychological condition of the mother during pregnancy monitoring so that the anxiety and worries of the mother before delivery can be resolved properly.